91.1k views
5 votes
-2(×+5)-7=3x+2(x-5) please solve the problem show your work do not solve for x​

User Jiang Bian
by
5.0k points

1 Answer

1 vote

Answer:

  • simplifies to -2x -17 = 5x -10
  • x = -1 . . . . the solution

Explanation:

-2(x+5)-7=3x+2(x-5) . . . . starting equation

-2x -10 -7 = 3x +2x -10 . . . eliminate parentheses using the distributive property

-2x -17 = 5x -10 . . . . . . . . . collect terms

-7 -2x = 5x . . . . . . . . . . . . . add 10

-7 = 7x . . . . . . . . . . . . . . . . . add 2x

-1 = x . . . . . . . . . . . . . . . . . . . divide by 7

User Kristoffer
by
5.0k points